Refuge : - Williams, Terry Tempest (Vintage Books, 2001)
In the spring of 1983 Terry Tempest Williams learned that her mother was dying of cancer. That same s[pring, Great salt Lake began to rise to record heights, threatening the Bear River Migratory Bird Refuge and with it the herons, owls, and snowy egrets that Williams, a poet and naturalist, had come to gauge her life by. One event was nature at its most random, the other a by-product of rogue technology: Terry's mother, and Terry herself, had been exposed to the fallout of atomic bomb tests in the 1950s.